Effect of Land Use and Land Cover Changes on Soil Erosion in Ethiopia - Bekele Tsegaye (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
Land degradation is one of a serious agricultural problem that posed severe threat to food production and the livelihood of peoples in Ethiopia. It resulted in high economic loss and threat in natural environment. The country loses about $106 million annually through soil and nutrient loss. Soil degradation is the one and the major form of land degradation that have been stayed for long period as the bottlenecks of the country's economy and human wellbeing. The economic loss soil degradation in the form of soil erosion and nutrient depletion only from the highlands of the country is about10-11% of agricultural gross domestic products. Soil erosion is one of the major causes of soil degradation in the country. The annual soil loss rate on average is about 42 tones/ha for croplands, and up to 300 tones/ha in extreme cases. The average total soil loss of the country is estimated as 12 ton/ha/year, which varied based on land cover types. Ethiopia historically passed significant dynamics in land use/land cover since long ago to date. Land use and land cover changes and degradation are increasing at alarming rate generally throughout the country. The change in land use types played a significant role in this increased rate of soil erosion in Ethiopia. Cultivated lands showed continuously increasing trend at the expense of forest and grasslands. The rapidly increasing population has led to a declining availability of cultivable land and a very high rate of soil erosion. The objective of this review paper is to view the effect of Land Use-Land Cover change in soil erosion in Ethiopia